Successful Collaboration in Social Care Practice: Beneficial Success Points of Interest for the Young Person in Swedish Juvenile Care (Journal of Comparative Social Work, 2018)
The aim of this ethnographic study is to analyse themes for ‘the successful collaborations’ that emerge from the study field notes on youth in Swedish juvenile care, and that can be interpreted as beneficial for these youth. These successful collaborations were observed, for instance, at meetings where the young persons were being discussed, and where an observer could distinguish planning for them that was carried out practically. The empirical base for this study is its total of 119 field observations/notes. The examples analysed reference a completed appointment for an eye test, a practical realization of active leisure, homework help and an internship placement that works. The coherence of three actors belonging to three different categories (coherent triads), and success points of interest that benefit the youth in the situation, create the image of a positive development for them. In this way, common identities of interplay that are useful for the young person are created and elucidated. The physical presence of the young person in these situations is an especially important theme for the ‘successful collaboration’. This study shows that trust and motivation are important aspects for a successful collaboration and inclusion of less powerful individuals and groups of individuals within a community. Young people discussed in this study receive confirmation of their identities by participating in the community, with a successful interaction between actors in juvenile care a prerequisite for successful involvement and integration.